Impact of sarcopenia on postoperative surgical site infections in patients undergoing flap reconstruction for oral cancer. Issue 5 (May 2020) - Nakamura, H.; Makiguchi, T.; Yamaguchi, T.; Suzuki, K.; Yokoo, S.
Abstract: Sarcopenia is characterized by progressive and generalized loss of skeletal muscle mass and strength. The aim of the study was to investigate the impact of skeletal muscle mass on surgical site infection (SSI) in flap reconstruction for defects after oral cancer resection. The subjects were a non-randomized, retrospective cohort of 106 patients who underwent this procedure after preoperative abdominal-lumbar computed tomography (CT). Cross-sectional areas (cm 2 ) of skeletal muscles in the L3 region were measured by manual outlining on CT images. These areas were then normalized for height (cm 2 /m 2 ) and defined as the skeletal muscle index (SMI). Recipient site SSI occurred in 28 patients (26.4%). Lower body mass index, haemoglobin and SMI were significantly related to recipient site SSI in univariate analysis ( P <0. 05). In a multiple logistic regression model, lower SMI was a significant risk factor for recipient site SSI (odds ratio = 3.95 per 10 cm 2 /m 2 decrease, P =0. 005). This result suggests that increasing skeletal muscle mass by exercise or nutrition before surgery may prevent recipient site SSI after resection of oral cancer and subsequent reconstruction.